Legal and ethical dimensions of AI in education: navigating new frontiers - Kronivets, Tetiana; Yakovenko, Olena; Tymoshenko, Yelyzaveta; Ilnytskyi, Mykhailo; Iasechko, Svitlana; Iasechko, Maksym (Review of Artificial Intelligence in Education, 2023)
Objective: This study critically examines the legal aspects of using artificial intelligence (AI) in education, exploring the roles of chatbots, Chat GPT, chat-based plagiarism issues, educational simulations, and AI's impact on the labor market. Methods: Employing a variety of research methods, the study analyzes current legal norms and international laws relevant to AI in education. This includes considerations of intellectual property, data privacy, ethical standards, and liability. Results: The paper highlights the challenge of chat-based plagiarism, emphasizing the need for careful information use to maintain academic integrity. While students might misuse AI tools like chatbots and GPT models for plagiarism, these technologies also aid in plagiarism detection. The study also explores the use of machine learning and data analysis in developing personalized learning experiences, enhancing learning effectiveness and knowledge retention. Conclusion: AI's integration into education promises to improve quality and accessibility, but necessitates a robust legal framework. The article evaluates the effectiveness of various AI tools, including chatbots, which provide on-demand information, and Chat GPT, useful for textual material handling. It also discusses the role of learning simulations in personalizing education, using AI to analyze performance data and tailor individual learning paths.